C-ABL in human cancer: an investigation of its role in apoptosis inhibition, differentiation and angiogenesis - Russell, Jennifer M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2003)
Research over the past number of decades has significantly advanced our understanding of the cell signalling effects that mediate a diverse array of cellular activities including cell proliferation, homeostasis and differentiation of both normal and cancer cells. Signal transduction within and between cells means that they can communicate important information and act upon it. Since signalling networks impinge on so many aspects of normal cellular function, it is not surprising that so many diseases have at least some basis in a signalling defect. Aberrant cell signalling has been implicated in the initiation, progression and metastasis of cancer. It is only recently that the molecular basis for these events has been studied, leading to the development of therapies that target one or more of the components of these series of events. Agents presently being evaluated as inhibitors of signal transduction include both natural and synthetic compounds, monoclonal antibodies and anti-sense oligonucleotides. Undoubtedly, a greater understanding of the precise role of individual proto-oncogenes and tumour suppressor genes in the development of human cancer will enable us to tailor more specific therapies.
Keywords: Histopathology, Ph.D.; Ph.D. Trinity College Dublin